The work-sociology of academic aeromobility at remote institutions - Hopkins, D; Higham, J; Orchiston, C (Routledge, 2019)
Theoretically framed by the concepts of networks, co-presence and proximity, we explore the interplay of corporeal and virtual academic mobilities in the context of ‘remote institutions’ to advance the work-sociology of aeromobility at a time of climate crisis. Empirical insights are drawn from 31 in-depth interviews conducted with academic staff at the University of Otago (New Zealand), to explore the complex personal and professional decisions that underpin academic mobility practices, and shed light on why levels of academic aeromobility have not diminished with the growing capacity for virtual substitution. Our findings inform discussion of the concepts of ‘necessary’ travel, and virtual travel as a substitute for non-participation. We conclude with reflections on the scope for social (practice) and institutional (policy) reform, and avenues of future research.